Strategi Triase dan Dukungan Keluarga dalam Optimalisasi Pelayanan Instalasi Gawat Darurat - Prima Prima; Rining S; Rafika Nurmalita Sari (Yayasan Inspirasi El Burhani, 2026)
Introduction: The Emergency Department (ED) is a critical service unit that requires rapid assessment and decision-making to ensure patient safety. The triage system plays a key role in prioritizing patients based on clinical severity. However, observations during a residency program at the Emergency Department of RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro revealed that family members often experienced anxiety and dissatisfaction due to limited understanding of the triage process and ineffective communication from healthcare providers. These issues frequently led to misconceptions regarding waiting times and perceptions of unequal service. Objective: This community service activity aimed to improve family members’ understanding of the triage process, reduce anxiety related to waiting time, and strengthen trust in emergency care services. Method: A descriptive participatory approach was used through observation of ED service flow and interviews with nurses to identify communication gaps. An educational intervention was implemented using an audiovisual medium in the form of a short animated video explaining triage categories, which was displayed in the ED waiting area. Family members’ knowledge was assessed using pre-test and post-test questionnaires. Results: Post-test results showed a clear improvement in family members’ understanding of triage compared to pre-test findings, where most participants initially demonstrated low knowledge levels. Qualitative observations indicated reduced complaints, improved cooperation during admission, and more effective communication between nurses and families, although variability in staff communication skills remained a challenge. Conclusion: Audiovisual-based education effectively improved family understanding of the triage process and supported better communication and trust in emergency services. Structured educational media and consistent communication strategies are recommended to sustain service quality improvements in the ED.